ANALYSIS OF THE CRIMINAL ACT OF ANIMAL ABUSE (STUDY OF DECISION NUMBER: 72/PID.C/2023/PN.PDG) - Vira Dalillah; Syaiful Munandar (DE'RECHTSSTAAT, 2024)
Asia For Animals Coalition announced that Indonesia is the country with the highest number of animal content uploaded on social media. There is 1,626 content showing animal abuse originating from Indonesia, according to data collected from YouTube, Facebook and TikTok between July 2020 and August 2021. However, there is still a lot of similar content from locations that have not been identified. Animal Defender Indonesia noted that the high number of animal abuse videos uploaded from Indonesia was due to "legal uncertainty". Doni Hedaru Tona, Chair of the Indonesian Animal Welfare Association, said that violence and torture against animals in Indonesia has different characteristics and levels of sadism. Many perpetrators of animal cruelty do this because they are motivated by profit. The reason why so much cruelty against animals occurs is because the perpetrators lack humanity and compassion so they are willing to carry out torture. Therefore, research was conducted entitled Analysis of the Crime of Pet Abuse (Decision Study number 72/Pid.C/2023/PN.Pdg). The formulation of the problem in this research is: What are the Forms of Crime Against Pets and How is the Analysis of Decision Number 72/Pid.C/2023/PN.Pdg Regarding Pet Abuse. This research uses normative research methods. The focus of the discussion is that Indonesian law has several regulations to protect animals from cruelty, including Article 302 paragraphs 1 and 2 of the Criminal Code which can result in a maximum prison sentence of two months for the perpetrator. However, there is a problem where judges are less strict in imposing sentences on perpetrators of animal abuse, especially if the perpetrator has committed this act repeatedly against the same pet. This can open up opportunities for the perpetrator in the future to repeat the act, because there is no deterrent effect felt by the defendant. The punishment imposed should be more severe to prevent the same behavior from recurring in the future.